Detection of Cannabinoid Receptor Expression by Endometriotic Lesions in Women with Endometriosis as an Alternative to Opioid-Based Pain Medication - Sarah Allam; Elizabeth Paris; Itzel Lazcano; Pincas Bitterman; Sanjib Basu; James O’Donnell; Animesh Barua (Journal of Immunology Research)
Emerging information suggests a potential role of medicinal cannabis in pain medication in addition to enhancing immune functions. Endometriosis is a disease of women of reproductive age associated with infertility and reproductive failure as well as chronic pain of varying degrees depending on the stage of the disease. Currently, opioids are being preferred over nonsteroidal anti-inflammatory drugs (NSAID) due to the latter’s side effects. However, as the opioids are becoming a source of addiction, additional pain medication is urgently needed. Cannabis offers an alternative therapy for treating the pain associated with endometriosis. Information on the use and effectiveness of cannabis against endometriotic pain is lacking. Moreover, expression of receptors for endocannabinoids by the ovarian endometriotic lesions is not known. The goal of this study was to examine whether cannabinoid receptors 1 and 2 (CB1 and CB2) are expressed by ovarian endometriotic lesions. Archived normal ovarian tissues, ovaries with endometriotic lesions, and normal endometrial tissues were examined for the presence of endometrial stromal cells using CD10 (a marker of endometrial stromal cells). Expression of CB1 and CB2 were determined by immunohistochemistry, immunoblotting, and gene expression studies. Intense expression for CB1 and CB2 was detected in the epithelial cells in ovarian endometriotic lesions. Compared with stroma in ovaries with endometriotic lesions, the expression of CB1 and CB2 was significantly higher in the epithelial cells in endometriotic lesions in the ovary (P<0.0001 and P<0.05, respectively). Immunoblotting and gene expression assays showed similar patterns for CB1 and CB2 protein and CNR1 (gene encoding CB1) and CNR2 (gene encoding CB2) gene expression. These results suggest that ovarian endometriotic lesions express CB1 and CB2 receptors, and these lesions may respond to cannabinoids as pain medication. These results will form a foundation for a clinical study with larger cohorts.